The prevalence of abdominal obesity according to the analysis of a representative group (Ожирение и метаболизм, 2008)
The combination of arterial hypertension (AH) and obesity is the focus of modern medicine due to the high prevalence of this phenomenon in modern society, an increased risk of cardiovascular complications, diabetes mellitus (DM) and premature death [1, 2, 3]. According to the World Health Organization, about 30% of the world population, of which 16.8% - 14.9% and women - men who are overweight [1] .In the present time for a more accurate designation of high cardiovascular risk patients with a typical combination of hypertension with abdominal obesity (AO), impaired glucose tolerance, and dyslipidemia, in clinical practice is widely used term "metabolic syndrome" (MS). The prevalence of MS in the population of developed countries, according to various estimates, ranging from 10 to 30%. According to special studies in patients with MS significantly increased risk of coronary heart disease, stroke, diabetes, and cardiovascular and total death [4, 5.6]. Isolation of this syndrome as a stable combination of several risk factors and occur when insulin sensitivity is of great practical importance. Changing lifestyles and adequate therapy can completely eliminate MS. This significantly reduces the risk of cardiovascular complications and diabetes [1, 2, 3]. To determine the true prevalence of MS in the population requires a fairly high costs associated with the need for appropriate laboratory studies. At the same time, the main, essentially obligate, namely a MS component AB, which may be readily determined by physical examination [7].